Engineering evolutionary intelligent systems - Abraham, Ajith; Grosan, Crina (Berlin : Springer, 2008)
"Evolutionary design of intelligent systems is gaining much popularity due to its capabilities in handling several real world problems involving optimization, complexity, noisy and non-stationary environment, imprecision, uncertainty and vagueness. This edited volume 'Engineering Evolutionary Intelligent Systems' deals with the theoretical and methodological aspects, as well as various evolutionary algorithm applications to many real world problems originating from science, technology, business or commerce. This volume is comprised of 15 chapters including an introductory chapter which covers the fundamental definitions and outlines some important research challenges. Chapters were selected on the basis of fundamental ideas/concepts rather than the thoroughness of techniques deployed."--Jacket
Gifted by Professor Ajith Abraham
Includes bibliographical references and index
Keywords: Evolutionary computation; Expert systems (Computer science)